An integral hybrid two-stage pulse tube cooler with improved efficiency. (March 2019) - Pang, Xiaomin; Wang, Xiaotao; Dai, Wei; Luo, Ercang; Li, Haibing; Ma, Suxia
Highlights: An integral hybrid two-stage pulse tube cooler is presented. The effects of key parameters of the stepped warm displacer have been studied in detail. A cooling power of 1.2 W is obtained at 20 K in experiments, corresponding to a relative Carnot efficiency of 5.42%. Abstract: This paper presented an integral hybrid two-stage pulse tube cooler, which works at liquid hydrogen temperature and uses stepped warm displacers as the phase shifter. The integral configuration with dual-opposed displacers and dual-opposed compressor pistons was adopted to improve the cooling performance and compactness of the system. Influences of key parameters of the stepped warm displacer on cooling performance were numerically analyzed. Based on the simulations, experiments were carried out. A cooling power of 1.2 W at 20 K was obtained with an input electric power of 303 W and the corresponding relative Carnot efficiency reached 5.42%. The influences of some operating parameters were also experimentally investigated.